Anatomy and ultrasonography of the bovine udder and teat - Tóth, Tamás; Kocsis, Róbert; Pajor, Ferenc; Póti, Péter; Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2018)
There is only a small number of Hungarian literature available concerning the anatomy and ultrasound examination of the bovine udder and teat. In this paper, the authors present the anatomical structure of the udder and the teat, the most commonly used ultrasound methods, and details of the ultrasound examination of a healthy udder and teat.
Keywords: cattle; udder; teat; anatomy; ultrasonography